Alcamo's Fundamentals of microbiology - Pommerville, Jeffrey C. (Jones & Bartlett Learning, 2014)
Foundations of microbiology -- The bacteria and archaea -- Bacterial diseases of humans -- Viruses and eukaryotic microorganisms -- Disease and resistance -- Control of microorganisms -- Microbiology and public health.